(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ayurveda has its own way of approach towards the management of Visha (Poison), Agadtantra is a special branch of Ashtang Ayurveda having its own importance in Visha Chikitsa. A general principle of treatment of poisoning is explained in Ayurvedic Samhitas (Treatises) like Charaka, Sushruta and Vagbhata. Acharya Charak has explained Twenty four modalities in the treatment of poisoning irrespective of animate or inanimate poisoning. Other scholars have stated specific treatment in the poisoning cases but still 24 modalities retains its importance. Toxicology also explains general treatment protocol for management of poisoning. The Protocol consists of vital establishment, removal of poison, use of antidote, general and psychiatric care of patient. But due to complexity of poisoning cases; General Treatment protocol becomes the guideline for the further management. When we compare both Ayurveda and modern medicine with respect to this aspect, we find that all these principles which are suggested by modern medicine are already described in Ayurvedic Samhitas before thousands of years. Chaturvimshati Upakrama (24 modalities) are like the treatment principle which directs the actual treatment regime in individual cases. General treatment protocol of poisoning is the modern replica of Acharya Charak’s Chaturvimshati Upakarama. A comparison of twenty four modalities with the general treatment protocol of poisoning is attempted in this review article.